Auction theory - Krishna, Vijay (Academic Press, 2002)
Through accessible, detailed examinations of themes central to auction theory, Vijay Krishna explores auctions and competitive bidding as games of incomplete information. His results on bidding strategies, efficiency, and revenue maximization, and his clear proofs for each proposition, make this book both the standard reference on auctions and the first source of authoritative information about multi-unit auctions. Well organized and featuring straightforward intuition, Auction Theory's depth and breadth lay bare the complexity and utility of this growing field. *The standard reference on auctions and the first source of authoritative information about multi-unit auctions *Explores auctions and competitive bidding as games of incomplete information *Uses accessible, detailed examinations of themes central to auction theory.